Azo dyes decolourisation by ABTS-oxidases (Laccases) from a fungus from tropical tree - Moin, Syed Faraz; Alfarra, Helmi Yousif; Omar, Muhammad Nor (Oriental Scientific Publishing Company, 2012)
Lignin is an important constitute of the wood and thus the organism like fungi and insects growing on wood produce some extracellular lignolytic enzymes. In fungi these enzymes include different oxidases and peroxidases. Lignin peroxidases, manganese peroxidases, versatile peroxidases and laccases have been characterised from fungi and their roles in wood decay has been established. Here we report ABTS-oxidases from an unidentified fungus isolated from tree bark sample from Kuantan, Malaysia. After the liquid media cultivation, the crude extracellular protein content was extracted and analysed by polyacrylamide gel electrophoresis. SDS-PAGE, native PAGE and zymography were carried out. Azo dyes, brilliant green, trypan blue, direct red 80 and eriochrome black T were used for decolourisation activity of the isolated fungus on solid medium. The results suggest that the extracellular proteins contain laccase enzyme activity. Out of the four azo dyes that were used for dye decolourisation assay, at least three were decolourised to different extents by the fungus.